A pet for Pat - Snow, Pegeen; Dunnington, Tom; Hillerich, Robert L., 1927- (Chicago : Childrens Press, 1984)
A young child receives a pet dog.
1.
1.5
-2.
K-3
Keywords: Children's stories, American; Dogs -- Fiction; Pets -- Fiction; Stories in rhyme; Dogs -- Fiction; Pets -- Fiction; Stories in rhyme